DEVELOPMENT OF CLIMBING CLOTHES USING COMPUTERIZED 3D CLOTHING SIMULATION - Viziteu, D.- R.; Curteza, A. (Art and Design, 2021)
The purpose. This paper aims to explore the applicability of computerized 3D virtual clothing simulation programs for the development of patterns for men’s rock climbing pants. Methodology. The experiment involved comparative methods of virtual wearing, as well as pressure points, perspective map and appearance evaluations. The theoretical and methodological basis of the research are scientific works presenting data from 3D virtual fitting software. Results. The study selected three designs of climbing pants to compare the layout of patterns and to analyze the appearance through virtual garment fit maps. First, the 2D-to-3D was applied to develop garment patterns of a rock climber’s pants. The patterns were developed directly in the 3D software. The flat patterns can be visualized in the sewing/assembly stage of the prototype. Then, 3D animation technology was used in simulation. The results throughout the study were: 1) 3D simulation of three different types of pants design. 2) Evaluating the fit and comfort of the clothing using garment fitting maps. 3) Identifying the most discomforting parts of the patterns, thigh, hip, waist, pants hem and knee girth. 4) Modify and adjust the clothing according to the evaluation situation. Scientific novelty consists in providing a systematic methodology of utilizing 3D simulation for a specific category of wearers, such as rock climbers. Practical significance. The considered research directions of 3D clothing simulation can be used by designers and patternmakers in the creative and experimental process of designing clothes expanding the possibilities of software to transform functional design in the industry and research.